2013
DOI: 10.1186/1472-6963-13-426
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of care for the physical health of patients with severe mental illness: a qualitative study assessing the view of patients and families

Abstract: BackgroundPatients with severe mental illness (SMI) experience more physical comorbidity than the general population. Multiple factors, including inadequate seeking of healthcare and health care related factors such as lack of collaboration, underlie this undesirable situation. To improve this situation, the logistics of physical health care for patients with SMI need to be changed. We asked both patients and their families about their views on the current organization of care, and how this care could be impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 13 publications
1
52
0
Order By: Relevance
“…A crucial organisational barrier in our findings was the dilemma and lack of clarity around service responsibility - mental health or physical health services - for provision of physical health care. Interestingly, this reflects previous International qualitative research whereby mental health and primary care health care systems have been found to operate in silo, resulting in no clear preference as to which physical-mental professional should provide the physical care [3]. However, our unique framework with specific relevance to physical-mental health domains may help to resolve this recurring dilemma for mental health professionals through ensuring transparency of service responsibility via coordinating care with physical professionals, and documenting those meaningful physical health care discussions and outcomes on a living care plan that either professionals may consult to clarify provision of physical health care, and to give context on their physical health needs.…”
Section: Discussionsupporting
confidence: 63%
“…A crucial organisational barrier in our findings was the dilemma and lack of clarity around service responsibility - mental health or physical health services - for provision of physical health care. Interestingly, this reflects previous International qualitative research whereby mental health and primary care health care systems have been found to operate in silo, resulting in no clear preference as to which physical-mental professional should provide the physical care [3]. However, our unique framework with specific relevance to physical-mental health domains may help to resolve this recurring dilemma for mental health professionals through ensuring transparency of service responsibility via coordinating care with physical professionals, and documenting those meaningful physical health care discussions and outcomes on a living care plan that either professionals may consult to clarify provision of physical health care, and to give context on their physical health needs.…”
Section: Discussionsupporting
confidence: 63%
“…) and it has been suggested that there is a need for clarifying the division of responsibilities of care and support provision across agency borders (van Hasselt et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Hence, there is a persistent need for further, larger and more comprehensive evaluations in other clinical settings. There are significant healthcare barriers to overcome to ensure that monitoring is undertaken [van Hasselt et al 2013], such as reducing uncertainty within clinical teams about whose 'responsibility' it is to undertake screening [Crabb et al 2009;Vasudev and Martindale, 2010], enhancing access to basic equipment, and improving the confidence of mental-health professionals in interpreting laboratory results [De Hert et al 2011]. Although there are logistic challenges in arranging screening for people with severe mental illness, significant opportunities for screening and interventions to reduce morbidity and mortality are being missed.…”
Section: Discussionmentioning
confidence: 99%